CONNECTION OF MATHEMATICS LESSONS AND LABOR EDUCATION IN PRIMARY CLASSES (Web of Technology: Multidimensional Research Journal, 2024)
Instability in the global market and the variability of technologies and methods in the 21st century give rise to the need for increased attention to 21st century skills, which can be developed in the context of any subject, including in the interdisciplinary interaction between mathematics and labor education, which is the focus of this article.